Upaya Kepolisian: Pelanggaran Lalu Lintas Terhadap Anak di Bawah Umur di Kota Padangsidimpuan - Wibowo, Putri Suci; Gunawan, Syafri; Siregar, Khoiruddin Manahan (Jurnal El-Thawalib, 2024)
This research examines the efforts of the police in preventing traffic violations by minors in Padangsidimpuan City. The research method used is field research with a qualitative approach. The primary data sources are the Traffic Unit (Satlantas) police at the Padangsidimpuan City Police, while secondary data includes books, previous studies and scientific journals that are considered relevant to this research. Data collection techniques with observation, interviews, and documentation, with qualitative descriptive data analysis techniques. The results of this study show that the police's efforts to prevent traffic violations by minors are carried out in three ways, namely first: Pre-emptive efforts by providing socialization to the community, second: Preventive efforts by providing direction and guidance through counseling, and third: Efforts Repressive by conducting raids, giving warnings and fines. Then the obstacles faced by the police in preventing traffic violations by minors are the lack of knowledge and legal awareness of the community so that they cannot understand the applicable laws, the manual ticket sanctions that have been abolished causing the public to commit traffic violations and the bad image of the police. lead to a lack of public trust in the police.